Nonpharmacological interventions to reduce behavioral and psychological symptoms of dementia: A systematic review - Oliveira, Alexandra Martini De; Radanovic, Marcia; Mello, Patrícia Cotting Homem De; Buchain, Patrícia Cardoso; Vizzotto, Adriana Dias Barbosa; Celestino, Diego L.; Stella, Florindo [UNESP]; Piersol, Catherine V.; Forlenza, Orestes V. (Hindawi, 2015)
Introduction. Behavioral and psychological symptoms of dementia (BPSD) are defined as a group of symptoms of disturbed perceptive thought content, mood, or behavior that include agitation, depression, apathy, repetitive questioning, psychosis, aggression, sleep problems, and wandering. Care of patients with BPSD involves pharmacological and nonpharmacological interventions. We reviewed studies of nonpharmacological interventions published in the last 10 years. Methods. We performed a systematic review in Medline and Embase databases, in the last 10 years, until June 2015. Key words used were (1) non-pharmacological interventions, (2) behavioral symptoms, (3) psychological symptoms, and (4) dementia. Results. We included 20 studies published in this period. Among these studies, program activities were more frequent (five studies) and the symptoms more responsive to the interventions were agitation. Discussion. Studies are heterogeneous in many aspects, including size sample, intervention, and instruments of measures. Conclusion. Nonpharmacological interventions are able to provide positive results in reducing symptoms of BPSD. Most studies have shown that these interventions have important and significant efficacy.